161k views
1 vote
Expand the expression:
a) (u + v)^3
b) (u + v)^4

User Metafaniel
by
6.2k points

1 Answer

1 vote

Answer:

(a)
(a+b)^3=a^3+b^3+3ab(a+b)=a^3+b^3+3a^2b+3ab^2

(b)
(u^2+v^2+2uv )(u^2+v^2+2uv)=u^4+u^2v^2+2u^3v+u^2v^2+v^4+2uv^3+2u^3v+2uv^3+4u^2v^2=u^4+v^4+4u^3v+4v^3u+5u^2v^2

Explanation:

We have to expand the expression

(a)
(u+v)^3 there are different methods for expanding the expression here u used algebraic identity for expansion

We know the algebraic identity


(a+b)^3=a^3+b^3+3ab(a+b)=a^3+b^3+3a^2b+3ab^2

(b)
(u+v)^4

We know the algebraic identity
(a+b)^2=a^+b^2+2ab


(u+v)^4 can be written as
(u+v)^2* (u+v)^2


(u^2+v^2+2uv )(u^2+v^2+2uv)=u^4+u^2v^2+2u^3v+u^2v^2+v^4+2uv^3+2u^3v+2uv^3+4u^2v^2=u^4+v^4+4u^3v+4v^3u+5u^2v^2

User Umesha D
by
5.6k points